Anti-Elastase Potential in Vitro of Koro Komak (Lablab Purpureus) Extract as Anti-Aging Protection - Naila Zanubah Arifah; Dina Helianti; Erfan Efendi (International Journal Labs, 2025)
The aging process leads to skin changes such as wrinkles and loss of elasticity, often accelerated by premature aging caused by factors like UV radiation and reactive oxygen species (ROS). Elastase, an enzyme responsible for degrading elastin in the skin’s extracellular matrix, plays a critical role in this process. This study aimed to investigate the anti-elastase potential of koro komak (Lablab purpureus) extract, a plant rich in polyphenolic compounds, through in vitro testing. A quasi-experimental design was employed, using different concentrations of the extract compared to ascorbic acid as a positive control. Phytochemical screening confirmed the presence of flavonoids, phenols, and tannins. The extract exhibited moderate anti-elastase activity with an IC?? value of 128 ?g/mL, and at 200 ?g/mL concentration, it inhibited elastase enzyme activity by 65.90%. These findings suggest that koro komak extract has promising potential as a natural anti-aging agent by protecting skin elasticity through elastase inhibition.